Three-dimensional-guided removal and preparation of dental root posts: concept and feasibility - Schwindling, Franz Sebastian; Tasaka, Akinori; Hilgenfeld, Tim; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of prosthodontic research, 2020)
Patients - This case report presents a novel method to remove glass fiber-reinforced composite root posts in a minimally invasive way while simultaneously shaping the canal for a new post-endodontic restoration. A multi-morbid, handicapped 62-year-old patient was referred with a horizontally fractured maxillary incisor presenting approximately 1 mm residual coronal tooth height. Endodontic revision was necessary, which required removal of a glass fiber-reinforced composite post. A cone-beam computed tomography (CBCT) scan was imported into conventional implant-planning software and matched to a stone cast of the intraoral situation. Position, length, and axis of the future post were planned virtually. Based on this planning, a tooth-supported splint was three-dimensionally (3D) printed. This splint allowed use of a 2.2-mm spiral drill for removal of the fractured post and shaping of the root canal for a new cast post-and-core. This metal post-and-core was adhesively cemented and prepared for a zirconia single crown veneered in the labial aspect. - Discussion - This method currently requires use of CBCT-based, ionizing 3D imaging. Additional refinements to this approach can be made regarding spiral drill design and coating as well as regarding the post-and-core workflow. - Conclusions - 3D-guided post-endodontic management is feasible. More research is needed to balance higher radiation doses against therapeutic success.
Available online 16 May 2019
Gesehen am 27.03.2020